Figure 9 in Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy - Bianucci, Giovanni; Landini, Walter (Zenodo, 2006)
Figure 9. Zygophyseter varolai gen. et sp. nov. Mandible (A–E) and isolated upper teeth (F, G) of the holotype (MAUL 229/1). A, anterior view; B, ventral view of the anterior portion of the symphysis; C, dorsal view; D, lateral view; E, medial view of left posterior portion of right dentary; F, lateral or medial views; G, posterior views. Published as part of Bianucci, Giovanni & Landini, Walter, 2006, Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy, pp. 103-131 in Zoological Journal of the Linnean Society 148 (1) on page 115, DOI:10.1111/j.1096-3642.2006.00228.x, http://zenodo.org/record/5427349